2004
DOI: 10.1109/tnet.2004.838602
|View full text |Cite
|
Sign up to set email alerts
|

DHTTP: An Efficient and Cache-Friendly Transfer Protocol for the Web

Abstract: Abstract-Today's HTTP carries Web interactions over clientinitiated TCP connections. An important implication of using this transport method is that interception caches in the network violate the end-to-end principle of the Internet, which severely limits deployment options of these caches. Furthermore, while an increasing number of Web interactions are short, and in fact frequently carry only control information and no data, TCP is often inefficient for short interactions We propose a new transfer protocol fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Michael Rabinovich and Hua Wang implemented Dual-Transport HTTP (DHTTP) which splits the traffic between UPD and TCP channels. This showed a significant performance improvement when the bottleneck is in the network [49]. HTTP over SCTP also benefits from faster page downloads and shorter response time [50].…”
Section: Protocol Optimizationmentioning
confidence: 97%
“…Michael Rabinovich and Hua Wang implemented Dual-Transport HTTP (DHTTP) which splits the traffic between UPD and TCP channels. This showed a significant performance improvement when the bottleneck is in the network [49]. HTTP over SCTP also benefits from faster page downloads and shorter response time [50].…”
Section: Protocol Optimizationmentioning
confidence: 97%
“…Dual-Transport HTTP (DHTTP) [67], a new transfer protocol for the web, was proposed by splitting the traffic between UDP and TCP channels based on the size of server response and network conditions. In DHTTP, there are two communication channels between a client and a server, a UDP channel and a TCP channel.…”
Section: ) Minimizing Http Requestsmentioning
confidence: 99%
“…The server responds to a request of 1460 bytes or less over the UDP channel, while the response to other requests will be transmitted over the TCP channel. The performance analysis performed in [67] shows that DHTTP significantly improves the performance of Web servers, reduces user latency, and increases utilization of remaining TCP connections. However, DHTTP imposes extra requirements on firewalls and network address translation (NAT) devices.…”
Section: ) Minimizing Http Requestsmentioning
confidence: 99%
See 1 more Smart Citation
“…Web traffic has dominated the Transmission Control Protocol (TCP) connections over the Internet today. Many studies [1][2][3][4] have shown that TCP is poorly suitable for web traffic due to its bursty, short-lived, and delay-sensitive properties [5]. As a result, it is imperative to develop efficient congestion control and buffer management schemes for effectively supporting Web traffic and investigate the impact of these schemes on network performance and Quality-of-Service (QoS).…”
Section: Introductionmentioning
confidence: 99%